Skin structure variation in water frogs of the genus Telmatobius (Anura: Telmatobiidae) - Barrionuevo, Jose Sebastian (2017)
Skin structure is studied in a broad sample of frog species of the genus Telmatobius and its relatives. These frogs exhibit different ecological habits and occupy different habitats. The results demonstrate that the coexistence of two types of serous glands, a rare feature among anurans, is widespread in Telmatobius. These types of serous glands, called type I and II, are characterized by the different size of the granules. However, some strictly aquatic species of the genus have only one type of serous glands (type I); this feature might be interpreted, within Telmatobius, as the result of independent losses of serous glands type II. Other finding was the occurrence of the Eberth-Kastschenko (EK) layer in the dermis in almost all studied species of Telmatobius. This result was unexpected because the EK layer is generally absent in aquatic anurans and was considered absent in Telmatobius. However, there are evident differences in its thickness that, combined with data of ecological habits and main habitats, reveal a complex pattern within Telmatobius, as well as among the other studied genera. Although we are far from understanding the significance of the presence of two types of serous glands in Telmatobius or the functions of the EK layer in general, these taxonomic and ecologic patterns could guide future research.